Single‐cell resolution in high‐resolution synchrotron X‐ray CT imaging with gold nanoparticles. (1st January 2014) - Schültke, Elisabeth; Menk, Ralf; Pinzer, Bernd; Astolfo, Alberto; Stampanoni, Marco; Arfelli, Fulvia; Harsan, Laura‐Adela; Nikkhah, Guido
<x xml:space="preserve">Abstract</x> Gold nanoparticles are excellent intracellular markers in X‐ray imaging. Having shown previously the suitability of gold nanoparticles to detect small groups of cells with the synchrotron‐based computed tomography (CT) technique both ex vivo and in vivo, it is now demonstrated that even single‐cell resolution can be obtained in the brain at least ex vivo. Working in a small animal model of malignant brain tumour, the image quality obtained with different imaging modalities was compared. To generate the brain tumour, 1 × 105 C6 glioma cells were loaded with gold nanoparticles and implanted in the right cerebral hemisphere of an adult rat. Raw data were acquired with absorption X‐ray CT followed by a local tomography technique based on synchrotron X‐ray absorption yielding single‐cell resolution. The reconstructed synchrotron X‐ray images were compared with images obtained by small animal magnetic resonance imaging. The presence of gold nanoparticles in the tumour tissue was verified in histological sections.